Co-occurrence of aflatoxins in plant oil products from China. Issue 4 (2nd October 2022) - Ji, Junmin; Jiang, Miaomiao; Zhang, Yaxin; Hou, Jie; Sun, Shangde
ABSTRACT: Aflatoxins have been detected as contaminants of oil crops before harvesting and drying, during storage and manufacturing and could be transferable to plant oils. There are more than 20 different types of aflatoxins, among which the most commonly occurring are the B1, B2, G1 and G2 . Concentrations of these four aflatoxins were determined in plant oils from retail shops in China and in crude peanut oil extracted from culled mouldy peanuts by HPLC with fluorescence detection. Overall, aflatoxins were present in 25 of the 63 samples. The four aflatoxins co-existed in vegetable oil, but the content of AFB1 was usually higher than the other aflatoxins. Particularly in the case of highly contaminated oil samples, AFB1 accounted for 68% of the total aflatoxins. According to the health risk assessment, the low margin of exposure values from AFB1 in oils suggests a high level of concern for children.